Heterogeneity, Characteristics, and Public Health Implications of Listeria monocytogenes in Ready-to-Eat Foods and Pasteurized Milk in China - Chen, Yuetao; Chen, Moutong; Wang, Juan; Wu, Qingping; Cheng, Jianheng; Zhang, Jumei; Sun, Qifan; Xue, Liang; Zeng, Haiyan; Lei, Tao; Pang, Rui; Ye, Qinghua; et al. (Frontiers in Microbiology, 2020)
Listeria monocytogenes is a foodborne pathogen with a high mortality rate in humans. This study aimed to identify the pathogenic potential of L. monocytogenes isolated from ready-to-eat (RTE) foods and pasteurized milk in China on the basis of its phenotypic and genotypic characteristics. Approximately 7.7% (44/570) samples tested positive for L. monocytogenes among 10.8% (39/360) RTE and 2.4% (5/210) pasteurized milk samples, of which 77.3% (34/44) had <10 MPN/g, 18.2% (8/44) had 10–110 MPN/g, and 4.5% (2/44) had >110 MPN/g. A total of 48 strains (43 from RTE foods and five from milk samples) of L. monocytogenes were isolated from 44 positive samples. PCR-serogroup analysis revealed that the most prevalent serogroup was II.2 (1/2b-3b-7), accounting for 52.1% (25/48) of the total, followed by serogroup I.1 (1/2a-3a) accounting for 33.3% (16/48), serogroup I.2 (1/2c-3c) accounting for 12.5% (6/48), and serogroup II.1 (4b-4d-4e) accounting for 2.1%. All isolates were grouped into 11 sequence types (STs) belonging to 10 clonal complexes (CCs) and one singleton (ST619) via multi-locus sequence typing. The most prevalent ST was ST87 (29.2%), followed by ST8 (22.9%), and ST9 (12.5%). Virulence genes determination showed that all isolates harbored eight virulence genes belonging to Listeria pathogenicity islands 1 (LIPI-1) (prfA, actA, hly, mpl, plcA, plcB and iap) and inlB. Approximately 85.4% isolates carried full-length inlA, whereas seven isolates had premature stop codons in inlA, six of which belonged to ST9 and one to ST5. Furthermore, LLS (encoded by llsX gene, representing LIPI-3) displays bactericidal activity and modifies the host microbiota during infection. LIPI-4 enhances neural and placental tropisms of L. monocytogenes. Results showed that six (12.5%) isolates harbored the llsX gene, and they belonged to ST1/CC1, ST3/CC3, and ST619. Approximately 31.3% (15/48) isolates (belonging to ST87/CC87 and ST619) harbored ptsA (representing LIPI-4), indicating the potential risk of this pathogen. Antimicrobial susceptibility tests revealed that >95% isolates were susceptible to 16 antimicrobials; however, 60.4% and 22.9% isolates were intermediately resistant to streptomycin and ciprofloxacin, respectively. The results show that several isolates harbor LIPI-3 and LIPI-4 genes, which may be a possible transmission route for Listeria infections in consumers.